2013
DOI: 10.1093/infdis/jit352
|View full text |Cite
|
Sign up to set email alerts
|

Serum Drug Concentrations Predictive of Pulmonary Tuberculosis Outcomes

Abstract: Low drug AUCs are predictive of clinical outcomes in tuberculosis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
422
2
12

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 395 publications
(454 citation statements)
references
References 42 publications
18
422
2
12
Order By: Relevance
“…191 This is because of the differential rapid elimination of some drugs in the regimen, leading to prolonged monotherapy with the drug that is not rapidly or extensively metabolised over tens to hundreds of rounds of bacterial replication. The in-silico study 181 predicted that 0·68% of patients would develop acquired drug resistance and MDR tuberculosis within 2 months despite 100% adherence, because of such differential pharmacokinetic variability of regimen components.…”
Section: Pharmacokinetic Variability and Acquired Drug Resistancementioning
confidence: 99%
See 4 more Smart Citations
“…191 This is because of the differential rapid elimination of some drugs in the regimen, leading to prolonged monotherapy with the drug that is not rapidly or extensively metabolised over tens to hundreds of rounds of bacterial replication. The in-silico study 181 predicted that 0·68% of patients would develop acquired drug resistance and MDR tuberculosis within 2 months despite 100% adherence, because of such differential pharmacokinetic variability of regimen components.…”
Section: Pharmacokinetic Variability and Acquired Drug Resistancementioning
confidence: 99%
“…The in-silico study 181 predicted that 0·68% of patients would develop acquired drug resistance and MDR tuberculosis within 2 months despite 100% adherence, because of such differential pharmacokinetic variability of regimen components. A prospective clinical study 191 in the same population was performed, and identified suboptimal drug concentrations due to pharmacokinetic variability as the cause of failure of therapy in more than 90% of patients. Acquired drug resistance, including MDR tuberculosis, was encountered in 0·7% of patients during the first 2 months, despite adherence to standard doses of isoniazid, rifampicin, pyrazinamide, and ethambutol.…”
Section: Pharmacokinetic Variability and Acquired Drug Resistancementioning
confidence: 99%
See 3 more Smart Citations